Experimental modal analysis of composite plates with low velocity impact damage - Ling, Ellyna Chok Yee (2018)
This research studies the dynamic characteristics change of kenaf/glass fiber hybrid composite under low velocity impact damage which can be used as an alternative for aircraft radome following the studies conducted by Haris (2014) and Jamal (2016) that proves the composite offers good dielectric and impact properties. The impact suffered by a composite will bring changes in dynamic characteristics. These changes can be used to assess the structural integrity, hence preventing catastrophic failure. Three materials (kenaf, glass and kenaf/glass fiber hybrid composites) were impacted beforehand with three impact levels (3, 6 and 9 Joules). The dynamic characteristics (natural frequency, damping and mode shapes) under vertically clamped and cantilevered boundary conditions for the materials are studied and compared. Experimental modal analysis is carried out with a roving hammer for 20 points on a 9.5 × 11.5 cm specimen and frequency response function (FRF) graphs are obtained to analyze the dynamic characteristics after curve fitting. In general, natural frequency decreases while damping increases with increasing damage level. Besides, cantilevered condition induced lower modes due to gravitational pull. Prior to damage, kenaf composite has highest damping due to its cellular structure that acts as a vibration absorber. To eliminate mass and geometrical effects on the materials, normalized modes are computed. It is found that glass fiber composite has highest frequency which corresponds to its high stiffness. Its frequency also decreases the most to a maximum of 35% when damage is induced, while kenaf suffered the least decrement at about 1 – 18%. It can be said that kenaf is useful in stalling damage progression; reducing effect of damage. This is proven when the percentage decrement of hybrid composite lies between the other two composites. The damping of glass fiber composite on the other hand increased significantly to a maximum of 38% upon impact. Using the threshold of 0.8 (ranging 0 to 1), modal assurance criterion (MAC) presented high correlation between two investigated modes; corresponds to the similar mode shapes obtained pre and post impact for all materials. This means that up to 9J impact damage, the structures can maintain dynamic characteristics within 20% tolerance. This knowledge is vital for damage tolerance evaluation (DTE) which is normally conducted for aircraft parts. Hence, the hybrid composite can be utilized as radome due to its good dielectric, impact and dynamic characteristics.